Migratory Falcons Reintroduction in the Kyrgyz Republic - Kadyr Momunaliev (Пернатые хищники и их охрана)
The Hadad international project in Kyrgyz is implementing in accordance with the program of the Kingdom of Saudi Arabia dedicated to 'brighter future for the environmental efforts and conservation projects'. This project is pursuing balanced and smooth reintroduction process of migratory falcons in order to restore sustainable biodiversity in Central Asian region. Through the joint efforts of the two teams, we established a base for transporting of 115 falcons from Saudi Arabia to the Kyrgyz Republic.